Development of balance training program to improve balance control among Malaysian sports schools athletes - Ai Choo Lee; Mohansundar Sankaravel; Fariba Hossein Abadi; Fairus Fariza Zainudin (IP Iermakov S.S., 2022)
Background and Study Aim. Complex sports specific movements often require balance ability. This is accountable for injury prevention as well. Balance control is vital to athletes for all sports activities. It is the objective of the current study to develop and identify balance training program effectiveness in improving dynamic balance among athletes in Malaysian National Sport Schools. Material and Methods. This study used a true experimental with control group design, involved dynamic balance control measures before and after intervention. A total of 72 male and female athletes were randomly assigned into experimental group or control group after screening process for eligibility. The experimental group underwent 12 sessions of balance training program and the control group continued their usual training routine. The Y-Balance Test was utilized to quantify dynamic balance for both groups. Data was analyzed using independent and paired sample t-test. Results. The study finding indicated that the experimental group demonstrated significant improvement in the post-test compared to pre-test (p = 0.000, p < 0.001) but no significant changes happened to control group (p = 0.353, p > 0.05). Independent t-test showed during post-test, the experimental group attained better score compared to the control group (p = 0.000, p < 0.001). Conclusions. It is suggested that coaches and athletes may include this balance training program in their training regimen, hoping to help in improving dynamic balance, thus, to reduce risk of lower extremity injuries. Future studies are suggested to increase more variances of balance training and make comparison on their effectiveness as a way to obtain a more effective training program.